Product Development of Various Life Cycles for Inventory Network Management System Development - Aruneshwar D.K; D. Rajasekar (International Journal of Supply Chain Management, 2018)
The present defense industry development, driven by the rising needs towards economical condition, has made numerous life cycle product remanufacturing into an imperative viewpoint in giving the answer for effective store network administration from as right on time as the outline arrange. Because of these strict needs, key resources are engaged in this examination, to give it an adaptable system to be actualized for different protection various life cycle products intended to be remanufactured. This paper talks about the writing survey done for inventory network administration, different life cycle products, remanufacturing forms and basic achievement calculates new product advancement. It is additionally intended to set the necessities for any protection products, of which ought to be intended to consolidate the different life cycle personality. The point has along these lines been to build up an attainable system that will be tried for distinguished safeguard products and decide if it is a necessity in the underlying plan of new product advancement. In outline, this exploration will give a superior observation and go about as a rule for new product advancement, especially for protection or other applicable modern products. The thought is novel to help product fashioners to work together with inventory network supervisors keeping in mind the end goal to hold the study of different life cycle products.